2020
DOI: 10.1111/anec.12739
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of P wave terminal force in lead V1 for atrial fibrillation: A meta‐analysis

Abstract: Background Several studies have explored the association between P wave terminal force in lead V1 (PTFV1) and risk of atrial fibrillation (AF) occurrence, but the results were controversial. This meta‐analysis aimed to examine whether abnormal PTFV1 could predict AF occurrence. Methods We searched PubMed, Embase, and Cochrane Library databases for articles published before August 25, 2018. Pooled odds ratios (ORs) of AF occurrence were calculated using random‐effects mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 32 publications
4
44
1
Order By: Relevance
“…Alternatively, our study may have been underpowered to find any prognostic significance of abnormal PTFV 1 . However, given the lack of survival difference between patients with and without abnormal PTFV 1 , it is unlikely that the abnormal PTFV 1 bears clinically significant meaning with regard to prognosis for patients with severe HF treated with CRT, and from our findings it seems as if abnormal PTFV 1 has limited applicable value in this very sick population in line with previous studies that have shown limitations of abnormal PTFV 1 in different study populations [44, 45]. Our results need to be confirmed in future studies before any conclusions can be made.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, our study may have been underpowered to find any prognostic significance of abnormal PTFV 1 . However, given the lack of survival difference between patients with and without abnormal PTFV 1 , it is unlikely that the abnormal PTFV 1 bears clinically significant meaning with regard to prognosis for patients with severe HF treated with CRT, and from our findings it seems as if abnormal PTFV 1 has limited applicable value in this very sick population in line with previous studies that have shown limitations of abnormal PTFV 1 in different study populations [44, 45]. Our results need to be confirmed in future studies before any conclusions can be made.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have identified several P-wave indices that are markers of LA dysfunction and associated with ischaemic stroke with or without AF [17-21, 23-25]. However, these markers of atrial cardiopathy remain most strongly associated with embolic strokes and have not been validated thoroughly in an ESUS cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Given that some of these P-wave indices require further mathematical functions such as multiplication that is required in PTFV1, this can result in the potential magnification of errors [27]. These aforementioned factors could have contributed to some of the heterogeneity in the evidence surrounding the associations of P-wave indices and AF detection as well as stroke in literature [21, 23].…”
Section: Discussionmentioning
confidence: 99%
“…As the left atrial pressure/volume loading rises, the depolarization duration of atrium may be prolonged [ 30 ]. Furthermore, Ren et al [ 11 ] discovered that PTFV1 could predict the diagnosis of tuberculous constrictive pericarditis, while a meta-analysis indicated that PTFV1 is a good predictor of atrial fibrillation occurrence in populations with or without cardiovascular diseases [ 10 ]. In the present study, we found that the incidence of poor outcomes including MACEs was obviously increased in patients with NSTE-ACS who manifested primary PTFV1 (+) at discharge and PTFV1 (+) during hospitalization, based on long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…P wave terminal force in lead V1 (PTFV1), referred to as the Morris index, is a product of the amplitude (mm) and time (s) of a terminal negative P wave when P waves are positive and negative in both directions, as first proposed by Morris et al [ 9 ] in 1964. Research has shown that abnormal PTFV1 values are related to left ventricular diastolic dysfunction, atrial fibrillation, congestive heart failure, stroke, and death, and they could indicate the severity of cardiac disease [ 10 15 ].…”
Section: Introductionmentioning
confidence: 99%